The walking school bus [book with audioplayer] - Friedland, Aaron; Mandela, Ndileka ([Library Ideas, LLC], 2024)
"Every morning, Shaka and his little sister Nandi walk with their father to school. Though the journey is long and hot, they arrive at school happy to see their friends and ready to learn. Then one day, their father gives them terrible news: he has to go work in a mine far away, and they won't be able to go to school anymore. The route is too dangerous for them to walk alone, so they'll have to stay home. But when they discover a yellow toy bus in the dirt, Shaka and Nandi let their imaginations run wild. Could they buy their own school bus? Or build one themselves? Their plans prove much harder than they thought--but just when they're about to give up, Shaka and Nandi come up with an ingenious solution to get to school, one that will take the whole community to help. With lively illustrations from Andrew Jackson Obol, The Walking School Bus is an engaging story that shows the challenges many children around the world face in accessing education, as well as the creativity and community spirit that can help overcome them."--